التضمنات التربوية في الحوار بين الآباء والأبناء في القرآن الكريم - Abdul Muhyi (The Faculty of Tarbiyah and Teacher Training associated with PSPII, 2016)
The research starts from the assumption that the al-Qur'an is the source of the main points of education. The research aims to uncover the stylistic values and educational implications of the conversation between father and son in the verses of the Holy Qur’an. The method used in this research is content analysis. The results showed that the conversation between father and son are available in 16 verses. The stylistic values include the jumlah insyãiyyah like al-amr, an-nahyi, al-istifhãm, an-nidã, and at-tamanny which is coming out from its original meaning. Additionally, it contains jumlah khabariyyah that comes out from its original meaning, al-îjãz wa 'l-ithnãb, al-Qasr, al-Fashl wa' l-washl, al-kinãyah, ath-thibãq, al-jinãs, at-tasybîh, al-isti'ãrah, at-tatmîm, and al-muqãbalah. While the educational values include the curriculum, teaching methods and techniques, the basics of good relationships and communication.